Investigations on The Utilization of Plastic Wastes as a Replacement of Cement in Concrete Paver Blocks. - Murungi, Waren (Kabale University, 2023)
Plastic wastes has been a silent threat to the environment and their disposal is a serious issue for waste management bodies in different areas. In today’s society, there are no any alternatives to plastic products like plastic bottles, bags, sheets among others. With all the efforts made to limit its use, the utility of such plastic products has been increasing day by day. On the contrary, concrete being the widely used construction material is facing problems due to unavailability of construction materials (Cement, Sand and Coarse aggregate). In the previous experimentations, various attempts were made to check the feasibility of plastic wastes used partially in concrete with respect to various properties of strength, water absorption, workability, durability and ductility of concrete. This paper aims to study the possibility of using plastic waste as a binding material instead of cement in the manufacturing of paver blocks. The study concentrates on plastics with a Polyethylene terephthalate basis. Plastic waste was melted and mixed with a varying proportion of sand after which the thorough mixture was casted into paver block moulds. After 28 days of curing, water absorption and compressive strength tests were carried out on the paving blocks. The test results obtained showed that the water absorption capacity of the plastic concrete paver blocks was better compared to the ordinary concrete paver blocks. The compressive strength of the plastic concrete paver blocks was slightly lower than that of ordinary concrete paver blocks. The 50% plastic content in paver blocks showed the best results and was recommended for the use of the plastic concrete paver blocks can be used on non-traffic and light traffic roads.